One-Step Preparation of Hydrophobic Surfaces Containing Hydrophilic Groups for Efficient Water Harvesting - Lyu, Pei (Langmuir : the ACS journal of surfaces and colloids, 2021)
Multifunctional surfaces that are favorable for both droplet nucleation and removal are critical for water-harvesting applications, but there still remain great challenges. Herein, we proposed a facile strategy to construct hydrophobic surfaces containing moderate hydrophilic groups to achieve both exceptional droplet nucleation and removal. Different from natural desert beetle-inspired water-harvesting materials, these surfaces utilize limited hydrophilic domains to condense fog, and transport of formed tiny droplets relies on a hydrophobic background. The total surface area of the presented hydrophobic fabric contains hydrophilic groups, and the areas for trapping fog have increased. This feature is optimized to enhance the droplet nucleation density, and the surface still has excellent liquid repellency, resulting in maximum water collection efficiency of the prepared surface reaching up to 3.145 g·cm-2·h-1, much higher than the most reported water-harvesting materials. Due to its high efficiency and scalability, we believe that the proposed strategy to construct hydrophobic surfaces containing hydrophilic groups has great practical value